Readiness of Tourism Village Management in Napal Jungur, Seluma Regency - Inda Lastari, Payu; Alimansyah, Alimansyah; Yogopriyatno, Jatmiko (Indonesian Journal of Social Science Research, 2025)
Tourism villages have become a vital strategy for rural economic development in Indonesia, yet many face significant management challenges that impede sustainable growth. This study examines the readiness of tourism management in Napal Jungur Tourism Village, Seluma Regency, employing a descriptive qualitative approach using Terry's management theory to analyze five key dimensions: self-audit, survey, objective, action, and communication. Data were collected through direct observation, semi-structured interviews with 25 key informants, focus group discussions, and document analysis, followed by SWOT analysis. The findings reveal an uneven readiness profile across management dimensions, with the SWOT coordinate analysis positioning Napal Jungur in Quadrant I (0.80, 0.69), indicating positive growth potential. Natural environment, active youth participation, and village government support represent significant strengths, while weaknesses include limited dining facilities, weak marketing, inadequate maintenance systems, and underdeveloped management expertise. Napal Jungur Tourism Village demonstrates promising potential for sustainable tourism development but requires strategic interventions to enhance management capacity, particularly in formalizing objectives, developing systematic management approaches, and improving communication strategies to facilitate the transition from establishment to consolidation phase of tourism development.